An Efficient Privacy and Integrity-Preserving Range Query Scheme over Unsorted Data in IoT Two-tiered Wireless Sensor Networks (International Journal of Mathematics and Physics, 2021)
In most existing privacy-preserving range-query schemes, sorting data items is extremely critical for enabling integrity verification over query results. In two-tiered WSNs, the data is collected by several sensors and send to a central node called the storage node. If data is not sorted, it is hard for the sink to verify query result integrity without sending all data items to the sink. To preserve data privacy on the storage node, the sensors must do sorting, and data is encrypted before it’s sent to the storage nodes since storage nodes are more vulnerable to adversary attacks than the sensor nodes. However, sensors are resource-constrained, yet the sorting process is resource-consuming. The higher the number of data items collected, the larger the number of resources required to sort the elements. In this paper, on top of proposing a scheme that assumes that the data is sorted, we also propose a scheme we call Probabilistic Verification Neighborhood chaining (PvNC) for both sorted and unsorted data that still preserves data and range-query privacy and to a great extent guarantee data integrity. Experimental results show that sensor nodes use less power using our PvNC for unsorted data than the existing schemes that require data to be sorted.